Linguistics and Some Aspects of Its Underlying Dynamics - Massimo Piattelli-Palmarini; Giuseppe Vitiello (Biolinguistics, 2015)
In recent years, central components of a new approach to linguistics, the Minimalist Program, have come closer to physics. In this paper, an interesting and productive isomorphism is established between minimalist structure, algebraic structures, and many-body field theory opening new avenues of inquiry on the dynamics underlying some central aspects of linguistics. Features such as the unconstrained nature of recursive Merge, the difference between pronounced and un-pronounced copies of elements in a sentence, and the Fibonacci sequence in the syntactic derivation of sentence structures, are shown to be accessible to representation in terms of algebraic formalism.